Polymorphism study of Cryptosporidium hominis gp60 subtypes circulating in Tunisia. (September 2017) - Essid, Rym; Chelbi, Hanen; Siala, Emna; Bensghair, Ines; Menotti, Jean; Bouratbine, Aïda
Abstract: Cryptosporidium spp. are a major cause of gastrointestinal diseases in humans worldwide. While a single subtype of Cryptosporidium hominis has been shown to be responsible for several large outbreaks related to water contamination in developed countries, little is known about the epidemiology of C. hominis in developing countries. This study reports the first genetic characterization of C. hominis at the subtype level in several human populations in Tunisia using the gp60 gene. Eighteen isolates were identified as C. hominis by a restriction fragment length polymorphism (RFLP) analysis. The prevalence of this species in different human populations ranges from 1.53% to 13.04% with a high prevalence being reported in immunocompromised children (13.04%) followed by patients with malignent myeloma (5.5%) and HIV-infected patients (4.59%). The gp60 analysis on C. hominis isolates, performed in 14 cases, showed the presence of a single subtype family: "Ia". Different subtypes were identified within this family (A11G1R1, A12R3, A23G1R1, A26G1R1, A27G1R1, A28G1R1). The IaA26G1R1 subtype was the most dominant subtype described in this area (50%). Despite the high genetic diversity of Cryptosporidium spp, a low heterogeneity at the subtype level was observed within C. hominis circulating in Tunisia. This distribution is an indicator for intensive and stable anthroponotic cryptosporidiosis in this region. Besides, the presence of a unique genotype in 5 HIV-infected patients attending the same hospital ward suggests the possible occurrence of hospital-acquired infection and underlines the need to implement preventive measures to avoid nosocomial transmission. Highlights: We identified C. hominis subtypes circulating in urban area in Tunisia. C. hominis was characterized by the dominance of the Ia subtype family. Several subtypes were identified within the Ia subtype family. The subtype IaA26G1R1 was the most dominant subtype in this area (50%).